Issues in Estimating the Employment Generated by Energy Sector Activities - Bacon, Robert (World Bank, Washingotn, DC, 2014)
Many recent studies and reports on the performance of the energy sector have focused on the employment generated by investment. Governments, planning their energy futures, are also interested in the job creation benefits and possible identification of skill shortages that may emerge from a large energy program. Employment created or supported by the energy sector is frequently an issue whenever government support is being considered or provided. The purpose of this issues paper is to provide a guide to using such figures or constructing such estimates, and focuses in particular on illustrating different approaches and methodologies used in the last decade in estimating employment created. The study does not aim to provide definitive estimates of the employment generation potential of different technologies. The paper begins with a brief review of the various reasons why studies have focused on the employment generated by energy sector activities. It then reviews the different categories of employment that are commonly measured and discusses the bottom-up and top-down methodologies widely used for estimating these employment levels. The second half of the paper reviews in some detail certain studies that provide useful insights into methodology, and illustrates some of their typical findings.